The effects of gamification in Business English classes on the motivation and engagement of Management study program students - Zizi Nurhikmah; Yasmin Farani (Universitas Merdeka Malang, 2025)
This study explores the impact of gamification on the motivation and engagement of first- semester students of English course. The research involved 71 undergraduate students of Management Program, University of Merdeka Malang, who participated in a series of gamified activities, including digital quizzes and role-play simulations. Data were collected through pre- and post-intervention surveys based on Keller’s ARCS model, classroom observations, and attendance/activity records. Results showed a significant increase in students’ motivation across all four dimensions of the ARCS model, Attention, Relevance, Confidence, and Satisfaction (p < 0.05), after the introduction of gamification. Students reported higher levels of interest, enthusiasm, and willingness to participate, with a noticeable improvement in engagement and classroom dynamics. The findings suggest that gamification effectively enhances language learning by making it more interactive, enjoyable, and relevant to real-world business contexts. The study highlights the potential of gamification to increase student engagement and motivation in higher education, especially in Business English courses, without replacing traditional teaching methods. It is recommended that educators integrate gamification thoughtfully to complement existing pedagogical practices and improve learning outcomes.